Functional and phylogenetic diversity of woody plants drive herbivory in a highly diverse forest. Issue 3 (24th January 2014) - Schuldt, Andreas; Assmann, Thorsten; Bruelheide, Helge; Durka, Walter; Eichenberg, David; Härdtle, Werner; Kröber, Wenzel; Michalski, Stefan G.; Purschke, Oliver
Summary: Biodiversity loss may alter ecosystem processes, such as herbivory, a key driver of ecological functions in species‐rich (sub)tropical forests. However, the mechanisms underlying such biodiversity effects remain poorly explored, as mostly effects of species richness – a very basic biodiversity measure – have been studied. Here, we analyze to what extent the functional and phylogenetic diversity of woody plant communities affect herbivory along a diversity gradient in a subtropical forest. We assessed the relative effects of morphological and chemical leaf traits and of plant phylogenetic diversity on individual‐level variation in herbivory of dominant woody plant species across 27 forest stands in south‐east China. Individual‐level variation in herbivory was best explained by multivariate, community‐level diversity of leaf chemical traits, in combination with community‐weighted means of single traits and species‐specific phylodiversity measures. These findings deviate from those based solely on trait variation within individual species. Our results indicate a strong impact of generalist herbivores and highlight the need to assess food‐web specialization to determine the direction of biodiversity effects. With increasing plant species loss, but particularly with the concomitant loss of functional and phylogenetic diversity in these forests, the impact of herbivores will probably decrease – with consequences for the herbivore‐mediated regulation of ecosystem functions.